Non-suicidal self-injury, youth, and the Internet: What mental health professionals need to know - Lewis Stephen P (Child and Adolescent Psychiatry and Mental Health, 2012)
Abstract Non-suicidal self-injury (NSSI) content and related e-communication have proliferated on the Internet in recent years. Research indicates that many youth who self-injure go online to connect with others who self-injure and view others’ NSSI experiences and share their own through text and videos platforms. Although there are benefits to this behaviour in terms of receiving peer support, these activities can introduce these young people to risks, such as NSSI reinforcement through the sharing of stories and strategies, as well as, risks for triggering of NSSI urges. Due to the nature of these risks mental health professionals need to know about these risks and how to effectively assess adolescents’ online activity in order to adequately monitor the effects of the purported benefits and risks associated with NSSI content. This article offers research informed clinical guidelines for the assessment, intervention, and monitoring of online NSSI activities. To help bridge the gap between youth culture and mental health culture, these essentials include descriptions of Community, Social Networking, and Video/Photo Sharing websites and the terms associated with these websites. Assessment of these behaviours can be facilitated by a basic Functional Assessment approach that is further informed using specific recommended online questions tailored to NSSI online and an assessment of the frequency, duration, and time of day of the online activities. Intervention in this area should initially assess readiness for change and use motivational interviewing to encourage substitution of healthier online activities for the activities that may currently foster harm.